The impact of the local conservative climate on generalised trust in Sweden - Sümeghy, Dávid (Publikon, 2021)
The rise of the radical right parties, with their anti-immigrant rhetoric, may amplify the generally observed negative impact of diversity on generalised trust. The impact of the conservative climate created by these parties is apparent at the national level, but the little research carried out in the field has yet to examine the role of their local political power. In Sweden, the literature suggests that the radical right Sweden Democrats party has a stronger anti-immigration and ethnonationalist rhetoric at the local level, which may reduce the generalised trust of residents by triggering conflict theory. Calculating the conservative climate based on the percentage of party representatives on local councils using multi-level modelling, we observe that the contextual effect of the conservative climate is present and reduces generalised trust. However, the underlying cause of this effect is not fully known. It can be traced back to the party’s local politics, the residents and the local media.